This Way Out: A Narrative of Therapy with Psychotic and Sexual Offenders - Abrahams, Joseph Isaac (Hamilton Books, 2010)
This Way Out, a report of work done six decades ago in Howard Hall, the maximum security section of St. Elizabeth's Hospital in Washington, D.C., is immediately pertinent to today's forensic and mental health crises. The two volumes of this work help fill a need for specific data on what transpires in psychotherapy, especially that of sexual and psychotic offenders. In an era prior to medication, the therapist employs a version of Freudian analysis and adapts it to groups, both large and small. A sophisticated program resulted, in which a spiritual component, messianism, is pivotal. The author relates this dramatic story through his narrative accounts of 629 sessions. Early in the work, he presents the microanalysis of a session, to make explicit what he and the members said and did to alter their severe personal and social alienation. An informal running commentary, journalist headlines, and annotated bibliography assist the reader in the exploration and comprehension of this extensive work.